Influence of the intrinsic properties of nanopipettes on sensing performance - Wenhao Ma; Rong Tian; Shixuan He; Shaoxi Fang; Bohua Yin; Yongjia Wang; Ting Weng; Wanyi Xie; Danqun Huo; Changjun Hou; Deqiang Wang (Chemical Engineering Journal, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Improving spatial resolutions of unmanned aerial vehicle hyperspectral images to predict grain yield and protein content in rice - Zhonglin Wang; Rong Hu; Mingming Hu; Huilai Yin; Tao Liu; Yufei Xie; Yangming Ma; Feng Yang; Feijie Li; Zhiyuan Yang; Yongjian Sun; Jun Ma (Precision Agriculture, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Achieving sustainable rice production with reduced nitrogen fertilization through unlocking soil organic nitrogen mineralization by alleviating microbial carbon limitation - Ning Su; Xiangmin Rong; Yao Liu; Junru Li; Runjia Yin; Guixian Xie; Yuping Zhang; Gongwen Luo (Field Crops Research, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Microbial interactions between Lactoplantibacillus plantarum and Rhodotorula mucilaginosa in the fermented fish juice system - Xiayin Ma; Bingqian Zhou; Lina Jiang; Mingyang Xie; Zhixing Rong; Shixian Yin; Faxiang Wang; Yongle Liu; Xianghong Li (Food Research International, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Evaluation of the safety, immunogenicity and protective effect of an attenuated Pseudomonas plecoglossicida strain ΔgacS as the live vaccine for the large yellow croaker (Larimichthys crocea) - Tian-Jing Kang; Su-Ming Zhou; Xiao Xie; Rong-Rong Ma; Dong Qian; Shan Jin; Fei Yin (Fish & Shellfish Immunology, 2024)

Two-step synthesis of coconut shell biochar-based ternary composite to efficiently remove organic pollutants by photocatalytic degradation - Shipeng Zhang; Rong Wang; Jinhua Zhu; Xiaoyan Xie; Mei Luo; Hailong Peng; Yude Liu; Fei Feng; Ronghui Shi; Wang Yin (Journal of Environmental Chemical Engineering, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Outer inflammatory protein of Helicobacter pylori impacts IL-8 expression, adherence, cell apoptosis and cell cycle of gastric cells independent of its copy number - Qiaoyun Zhao; Wenzhu Yin; Rulin Zhao; Youhua Wang; Conghua Song; Huan Wang; Jianfang Rong; Fangfei Wang; Yong Xie (Medical Microbiology and Immunology, 2020)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Isolation an Aldehyde Dehydrogenase Gene from Metagenomics Based on Semi-nest Touch-Down PCR - Rong Chen; Chenglu Li; Xiaolin Pei; Qiuyan Wang; Xiaopu Yin; Tian Xie (Indian Journal of Microbiology, 2014)

Discovery of a novel esterase subfamily sharing an identified arm sequence (ArmEst) by gene-specific metagenomic PCR - Ao Zhang; Rong Zhao; Peng Jin; Lifang Ma; Xiaolong Xiong; Tian Xie; Xiaolin Pei; Li Yu; Xiaopu Yin; Qiuyan Wang (Biotechnology Letters, 2013)

Addition of Co2+ to culture medium decides the functional expression of a recombinant nitrile hydratase in Escherichia coli - Xiaolin Pei; Qiuyan Wang; Chenglu Li; Xiaopu Yin; Rong Chen; Tian Xie (Biotechnology Letters, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Characterization of a human Sec14-like protein cDNA SEC14L3 highly homologous to human SPF/TAP - Xin Ye; Chaoneng Ji; Gang Yin; Rong Tang; Li Zeng; Shaohua Gu; Kang Ying; Yi Xie; Robert Chunhua Zhao; Yumin Mao (Molecular Biology Reports, 2004)

The Immunoregulation of Mice by Somatic Transgenic Expression of Porcine Interleukin-6 Gene and CpG Sequence - Jiangling Li; Rong Gao; Mei Wu; Mingjie Meng; Manshu Tang; Yi Shen; Lihuan Wang; Xueyan Wu; Xue Yin; Hongguan Xie; Shigui Liu (Veterinary Research Communications, 2004)

Ribozyme-mediated resistance to rice dwarf virus and the transgene silencing in the progeny of transgenic rice plants - Shengcheng Han; Zujian Wu; Huaiyi Yang; Rong Wang; Yin Yie; Lianhui Xie; Po Tien (Transgenic Research, 2000)